The only thing worth dying for : how eleven Green Berets forged a new Afghanistan - Blehm, Eric (HarperCollins, 2010)
The author exposes the realities of unconventional warfare and nation-building in Afghanistan in this chronicle of one of the most important military mission in the early days of the Global War on Terror--ODA 574--wherein a Special Forces team infiltrated the mountains of southern Afghanistan, fomented a tribal revolt, and forced the Taliban to surrender.